2007
DOI: 10.1016/j.amjcard.2006.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Circulating Endothelial Progenitor Cell Colony-Forming Capacity and Migratory Activity in Middle-Aged Adults

Abstract: Middle-aged women have a lower prevalence and incidence of cardiovascular events than men. The mechanisms responsible for this sex-specific difference are unclear. Numerical and functional impairment of bone marrow-derived circulating endothelial progenitor cells (EPCs) is associated with increased cardio-and cerebrovascular morbidity and mortality. It is currently unknown whether there are sex-related differences in EPC number and function in middle-aged adults. We tested the hypothesis that EPCs isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
50
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 16 publications
14
50
2
2
Order By: Relevance
“…Indeed, we have previously reported gender-related differences in several aspects of endothelial health and function. 45,46 Third, the lack of a nonexercising control group is a shortcoming of our intervention study. However, the exercise training program used in the present study has consistently been shown to improve endovascular function in healthy adult humans varying in age and body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously reported gender-related differences in several aspects of endothelial health and function. 45,46 Third, the lack of a nonexercising control group is a shortcoming of our intervention study. However, the exercise training program used in the present study has consistently been shown to improve endovascular function in healthy adult humans varying in age and body composition.…”
Section: Discussionmentioning
confidence: 99%
“…In one study on a healthy middle-aged population without known cardiovascular risk factors, it has been demonstrated that women exhibited a distinctly higher EPC colonyforming capacity (approximately 150%) and greater migratory activity (40%) compared with men (80). Moreover, human women with a higher plasma estrogen concentration showed a significantly higher level of circulating EPCs.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…14 Endothelial progenitor cells from male donors are less migrative and form fewer colonies. 15 Bone marrow stem cells from female donors are more effective at functionally repairing cardiac ischemia than the same cells from male donors. 16 Osteoprogenitors derived from female rat bone increase proliferation and differentiation in response to progesterone, while the same cells from male rats do not.…”
mentioning
confidence: 99%